Clinical and X-ray Characteristics of Osteoradionecrosis of the Jaws and Related Factors - Hong, Dinh Dieu; Trieu Hung, Dang; Ngoc Anh Khoa, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 3, 2021)
This retrospective cohort study was conducted on 73 patients diagnosed with Osteoradionecrosis of the Jaws (ORNJ), treated in the Department of Maxillofacial Surgery of  the National Hospital of Odonto – Stomatology to describe some criteria including clinical symptoms, radiographic images and related factors of ORNJ in these patients by consulting medical records and interviewing patients. The study results show that the majority of lesions presented in the mandible, particularly in the angle region. The prominent symptoms were deep pain, fistula, exposed necrotic bone, tingling and numbness in the lips and cheeks, and trimus. Radiographic feature was ill-defined cortical destruction without sequestration. The patients’ major oral health problems  were poor dental hygiene and periodontitis. The related factors were tooth extraction, non-standard dental prosthesis and even root canal treatment. Keywords: Osteoradionecrosis of the jaws , clinical symptoms, radiography images, related factors. References [1] N. M. H. McLeod, M. C. Bater, P. A. Brennan, Management of Patients at Risk of Osteoradionecrosis: Results of Survey of Dentists and Oral & Maxillofacial Surgery Units in The United Kingdom, and Suggestions for Best Practice, British Journal of Oral and Maxillofacial Surgery, Vol. 48, No. 4, 2010, pp. 301-304, https://doi.org/10.1016/j.bjoms.2009.06.128. [2] S. Beaumont, N. Bhatia, L. McDowell et al., Timing of Dental Extractions in Patients Undergoing Radiotherapy and the Incidence of Osteoradionecrosis: A Systematic Review and Meta-analysis, British Journal of Oral and Maxillofacial Surgery, Vol. 59, No. 5, 2021, pp. 511-523, https://doi.org/10.1016/j.bjoms.2020.10.006. [3] A. Chronopoulos, T. Zarra, M. Ehrenfeld, S. Otto, Osteoradionecrosis of the Jaws: Definition, Epidemiology, Staging and Clinical and Radiological Findings. A Concise Review, International Dental Journal, Vol. 68, No. 1, 2018, pp. 22-30, https://doi.org/10.1111/idj.12318. [4] T. Reuther, T. Schuster, U. Mende, A. Kübler, Osteoradionecrosis of the Jaws as a Side Effect of Radiotherapy of Head and Neck Tumour Patients – A Report of a Thirty Year Retrospective Review, International Journal of Oral & Maxillofacial Surgery, Vol. 32, No. 3, 2003, pp. 289-295, https://doi.org/10.1054/ijom.2002.0332. [5] J. Silvestre-Rangil, F. J. Silvestre, Clinico-therapeutic Management of Osteoradionecrosis: A Literature Review and Update, Medicina Oral Patologia Oral y Cirugia Bucal, Vol. 16, No. 7, 2011, pp. e900-904, https://doi.org/10.4317/medoral.17257. [6] S. M. Mallya, S. Tetradis, Imaging of Radiation- and Medication-Related Osteonecrosis, Radiologic Clinics of North America, Vol. 56, No. 1, 2018, pp. 77-89, https://doi.org/10.1016/j.rcl.2017.08.006. [7] B. R. Goldwaser, S. K. Chuang, L. B. Kaban, M. August, Rick Factor Assessment for the Development of Osteoradionecrosis, Journal of Oral and Maxillofacial Surgery, Vol. 65, No. 11, 2007, pp. 2311-2316, https://doi.org/10.1016/j.joms.2007.05.021. [8] J. J. Thorn, H. S. Hansen, L. Specht, L. Bastholt, Osteoradionecrosis of the Jaws: Clinical Characteristics and Relation to the Field of Irradiation, Journal of Oral and Maxillofacial Surgery, Vol. 58, No. 10, 2000, pp. 1088-1093, https://doi.org/10.1053/joms.2000.9562. [9] I. J. Lee, W. S. Koom, C. G. Lee et al., Risk Factors and Dose-effect Relationship for Mandibular Osteoradionecrosis in Oral and Oropharyngeal Cancer Patients, International Journal of Radiation Oncology - Biology - Physics, Vol. 75, No. 4, 2009, pp. 1084-1091, https://doi.org/10.1016/j.ijrobp.2008.12.052. [10] B. S. Raggio, R. Winters, Modern Management of Osteoradionecrosis, Current Opinion in Otolaryngology & Head and Neck Surgery, Vol. 26, No. 4, 2018, pp. 254-259, https://doi.org/10.1097/MOO.0000000000000459. [11] K. Katsura, K. Sasai, K. Sato et al., Relationship Between Oral Health Status and Development of Osteoradionecrosis of the Mandible: a Retrospective Longitudinal Study, Oral Surgery Oral Medicine Oral Pathology Oral Radiology, Vol. 105, No. 6, 2008, pp. 731-738, https://doi.org/10.1016/j.tripleo.2007.10.011. [12] H. Abed, M. Burke, S. Scambler et al., Denture Use and Osteoradionecrosis Following Radiotherapy for Head and Neck Cancer: A Systematic Review, Gerodontology, Vol. 37, No. 2, 2020, pp. 102-109, https://doi.org/10.1111/ger.12456.